A Study On Conceptual Metaphors Of “Rain”/ “Mưa” , “Sunshine”/ “Nắng” In English Vs Vietnamese 20th Century Songs - Nguyễn Thị Khánh Ly (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This study aims at conducting a contrastive analysis of conceptual metaphor of “rain”/ “mưa”, “sunshine”/ “nắng” in English vs Vietnamese 20th century songs in the light of cognitive linguistics. The descriptive and contrastive methods are used in combination with the qualitative and quantitative approaches in order to help the researcher achieve the aims and objectives proposed. The data analysis is taken from approximately 300 songs in both English and Vietnamese with about 360 samples of conceptual metaphors of “rain”/ “mưa” and “sunshine”/ “nắng” in total. At the result, we have figured out 6 conceptual metaphors of “rain”/ “mưa” and 7 conceptual metaphors of “sunshine”/ “nắng” in both languages. The study has pointed out the similarities as well as the differences of conceptual metaphors of “rain”/ “mưa” and “sunshine”/ “nắng” in English and Vietnamese. Besides giving an in-depth understanding of conceptual metaphors of “rain”/ “mưa” and “sunshine”/ “nắng” in both languages, the research is carried out w